Islamic Educational Values in The Hadith on Hijrah - Thaib, Muhammad Ichsan (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
The concept of hijrah in Islam is not only interpreted as a physical movement from one place to another, but also encompasses profound spiritual and moral dimensions. The hadiths of the Prophet Muhammad Saw, particularly those concerning the intention and hijrah, contain many educational values ​​that can serve as a basis for developing the character and spirituality of students in Islamic education. This study aims to examine the Islamic educational values ​​contained in the hadiths about hijrah. The research method used is qualitative-descriptive, with data collection techniques through a literature review of primary sources in the form of hadith books such as Sahih Bukhari and Sahih Muslim, as well as secondary sources from hadith interpretation and Islamic education literature. The results show that the concept of hijrah in the hadith reflects educational values ​​such as sincerity, commitment to religious teachings, self-transformation. These values ​​are highly relevant in shaping the character of students in the modern era, where moral and spiritual challenges are increasingly complex. This research contributes to strengthening the Islamic education curriculum based on prophetic values ​​derived from the Prophet's hadith.